Ocurrence of the sea anemone Telmatactis panamensis (Verrill, 1869) (Cnidaria: Anthozoa: Actiniaria) at Isla del Coco National Park, Costa Rica - Fabián H. Acuña; Jorge Cortés; Agustín Garese (Revista de Biología Tropical, 2012)
The sea anemone fauna of Isla del Coco National Park (also known as Cocos Island Nacional Park), Pacific Costa Rica is poorly known. In the present work we report the first occurrence of the species Telmatactis panamensis. Individuals of this sea anemone (n=24) were collected at Chatham Bay intertidal and at 15m depth in Punta Ulloa, in both cases attached to rocks; during the expedition UCR-UNA-COCO-I in April 2010. We provide photographs of live individuals, external anatomy and an inventory of cnidae of the studied specimens. Possibly this species is extended to greater depth as observed by other authors in the Galápagos Islands. La fauna de anémonas de mar es prácticamente desconocida para el Parque Nacional Isla del Coco (Costa Rica). En el presente trabajo se reporta por primera vez la presencia de la especie Telmatactis panamensis. Individuos de esta anémona de mar fueron colectados en el intermareal de Bahía Chatham y a 15m de profundidad en Punta Ulloa, en ambos casos adheridas a rocas; durante la expedición UCR-UNA-COCO-I en Abril de 2010. Se proveen fotografías de ejemplares vivos, datos de su anatomía externa y un inventario del cnidae de los especímenes estudiados. Posiblemente esta especie se extienda a mayor profundidad, tal como fue observado por otros autores para ejemplares de las Islas Galápagos.